Adaptação familiar ao diagnóstico de Transtorno do Espectro Autista: uma compreensão da vivência de famílias - Tertuliano Leoni, Pedro Henrique; Jabali, Marisa Brufato Ferraz Capuzzo; Rodrigues, Alessandra Ackel (Revista Interdisciplinar de Saúde e Educação, 2020)
No Transtorno do Espectro Autista (TEA) encontram-se presentes déficits persistentes na comunicação e interação social em diversos contextos, além de padrões de comportamento e interesses repetitivos. Cada família adapta-se de modo distinto frente ao impacto do diagnóstico, seja pela atenção demandada aos familiares ou pelas emoções ambivalentes que tal patologia desperta. Objetivos: Investigar a adaptação familiar ao TEA em decorrência do diagnóstico na família por meio de um estudo qualitativo. Métodos: O estudo foi aprovado pelo comitê de ética e oito participantes, oriundos de quatro famílias participaram de uma entrevista semiestruturada com questões acerca da adaptação familiar. Os relatos foram submetidos à análise de conteúdo de Bardin. Resultados: Emergiram quatro categorias dos relatos: "Impacto do diagnóstico" (313), "Adaptação Familiar" (194), “Redes de apoio” (148) e "Perspectivas de futuro" (101). Discussão: O diagnóstico de TEA promove uma importante adaptação na família, a qual está associada a um nível de estresse significativo, que pode interferir diretamente nas práticas de cuidado dos familiares em relação ao autista. O suporte social oferecido por familiares, amigos e também por profissionais de saúde, educação e instituições pode contribuir para minimizar os efeitos do estresse, favorecendo a adaptação familiar. Conclusões: Faz-se necessário um olhar integral às famílias que recebem o diagnóstico de TEA, considerando-se a complexidade do processo de adaptação que vivenciam.Abstract: In the Autism Spectrum Disorder (ASD) it can be found present persistent deficits in communication and social interaction in diverse contexts, in addition to behaviour patterns and repetitive interests. Each family adapts differently to the impact of the diagnosis, either by the attention demanded by the family members or by the ambivalent emotions that such pathology arouses. Objectives: To investigate family adaptation to ASD in consequence of the diagnosis in the family by means of a qualitative. Methods: After the approval by the ethical committee in research, for data collection it was used the Perceived Stress Scale (PSS), the Medical Outcomes Study Social Support Survey (MOS-SSS) and the Scale of parenting beliefs and caring practices in both studies, associated with a semi-structured interview in the qualitative one and a characterization script in the quantitative one. Results study: Four families which were found by means of non-probabilistic sampling of snowball participated, totaling eight participants. After the transcription and thematic analysis of content of the interviews, eight categories emerged from the reports: “ASD” (191 times), “Impact of diagnosis” (313), “Family adaptation” (194), “Treatment” (100), “Beliefs” (69), “Support network” (148), “Future perspectives” (101) and “Families messages” (16). Discussion: The diagnosis of ASD promotes an important family adaptation, which is associated with a significant level of stress, that may interfere directly in the care practices of family members in relation to the autistic. The social support offered by family members, friends and also health and education professionals and also institutions may contribute to minimize stress effects, favouring family adaptation. Conclusions: It is necessary a comprehensive look at the families that receive the ADS diagnosis, considering the complexity of the adaptation process they experience.Keywords: Autism Spectrum Disorder. Family adaptation. Perceived stress. Support network. Parental beliefs.